Exploring Adolescent Mental Health Issues and Primary Service Needs in Wetland Areas: A Mixed-Method Study - Tampubolon, Nurhannifah Rizky; Tampubolon, Masrina Munawarah; Sari, Niken Yuniar (Jurnal Keperawatan Soedirman, 2025)
Limited awareness and restricted access to mental health screenings and services persist, largely due to the demands of academic commitments. The aim of this study is to describe the mental health issues faced by adolescents and exploring primary service needs in the wetland areas of Pekanbaru, Indonesia. A convergent parallel mixed methods approach was employed. Quantitative data were gathered using the Strengths and Difficulties Questionnaire (SDQ) to assess the mental health status of 276 adolescents. Qualitative data were collected to explore adolescents' primary health service needs through FGD with 21 participants, including stakeholders, health providers, and adolescents. The survey revealed that 48.2% of adolescents experienced mental health problems, with 26.5% falling into the abnormal category. Qualitative findings indicated that adolescents often neglect their mental health and rarely seek professional help. There is a significant need for parental involvement in mental health programs, and the integration of these programs within schools and communities is deemed essential for comprehensive care. In conclusion, addressing the mental health needs of adolescents requires a multifaceted approach, parental involvement, and the integration of mental health programs within existing health and educational systems. Ensuring affordability and quality of care remains crucial for effective adolescent mental health services.